Are Banks Different? Evidence from International Data - Claudia M. Buch (Kiel Institute of World Economics (IfW), 2000)
Pecking order models of international finance suggest that countries should become less reliant on international bank lending as they develop. Reduced information costs are one of the factors behind this trend towards disintermediation. This paper presents a simple model on the choice between bank debt and bond finance which builds on Rajan (1992), and it uses two new datasets to test the implications, focusing on bilateral cross-border bank claims and bond holdings. We find support for the hypothesis that the state of development of an economy lowers the share of bank finance. However, evidence on the importance of variables which more directly measure information costs is less clear-cut.
Keywords: F3; 330; international bank lending; international portfolio investment; Internationale Finanzierung; Portfolio-Investition; Kapitalstruktur; Kredit; Securitization; Anleihe; Entwicklungsstufe; Schätzung; OECD-Staaten; Welt